Novel N-phenyl-2-(aniline) benzamide hydrochloride salt development for colon cancer therapy - Peng, Yan; Peng, Ying; Zhang, Wei; Zhang, Siyi; Peng, Huiqian; Li, Zhen; Li, Bo; Liu, Linyi; Zhuo, Linsheng; Wang, Zhen; Wu, Junbo; Jiang, Weifan (Frontiers in Pharmacology, 2024)
N-phenyl-2-(aniline) analog N53 is a previously discovered dual inhibitor of Topo I and COX-2, which exhibited significant anti-colon cancer activity in vitro, but the poor solubility and moderate anti-cancer activity in vivo hindered its further development. To rectify the suboptimal drug properties of N53, a series of salt forms were developed. Among them, the hydrochloride (N53·HCl) has a well-characterized crystal structure and its solubility reached 540.1 µg/mL, which is nearly 1700 times higher than that of N53 (0.32 µg/mL). Increasing the N53 solubility consistently promotes its effective concentration, further enhancing the COX-2/Topo I inhibitory activity and the anti-tumor activity in vitro (IC50 values of 2.95 ± 0.08 µM for HT29 cells, 7.99 ± 0.85 µM for RKO cells, 10.94 ± 1.30 µM for HCT116 cells), as well as the anti-proliferative and pro-apoptotic activity. Meanwhile, its oral pharmacokinetic property in vivo is also improved. The elimination half-life (T1/2) is prolonged from 10.78 to 22.29 hours, the maximum plasma concentration (Cmax) is increased 2-fold, and the area under the plasma drug concentration-time curve (AUC0-) is increased 3-fold. In colon cancer xenograft mouse models of colon cancer, the tumor inhibition rate of N53·HCl was 53.7%, superior to that of N53 (34.7%). Moreover, the results of HE staining showed that N53·HCl had no obvious toxic effects and side effects on other organs, indicating that it was safe in vivo. In general, this study demonstrated that N53·HCl exhibits superior pharmacokinetic properties, anti-colon cancer efficacy, and safety, providing a promising drug candidate for colon cancer therapy.